44 THE RELATIONSHIP OF DIGIT RATIOS (2D:4D) TO AGGRESSIVE BEHAVIOR IN PATIENTS WITH TYPE 2 DIABETES OR LOW BACK PAIN. Issue 1 (1st January 2007) - D'Auria, A.; Martin, J. T.; Wilson, K.; Nicoll, T. K.
Abstract : The ratio of the second digit to the fourth digit (2D:4D ratio) has been noted in previous studies to be a sexually dimorphic trait. Women tend to have 2D:4D ratios closer to a value of one, whereas men tend to have 2D:4D ratios of less than one. We postulated that females with lower 2D:4D ratios would have higher levels of aggression. To test this hypothesis we examined patients, staff, or visitors at four hospitals and clinics in Southern California. Aggression was measured by a questionnaire based on the Leifer-Roberts Response Hierarchy, which included 18 questions based on three potential scenarios involving the subject. Second and fourth digits on each hand were measured in triplicate with calipers and the ratio of the second to the fourth digit on each hand was analyzed separately. Our study included 187 females and 95 males all between the ages of 18 and 60 in three treatment groups: diabetes, low back pain, or no health problems. Males scored significantly higher on the test instrument than females, thus validating this instrument for distinguishing sex differences in aggression. On the left-hand ratio, contrary to our hypothesis, we found that aggression was directly related to the 2D:4D ratio when all subjects were combined ( r = .18; p = .004) and when females were examined separately ( r = .20; p = .008), but the relationship was not statistically significant in males or in any treatment group alone. Moreover, on the right hand, a positive relationship between 2D:4D ratio and aggression was found in male and female diabetics ( r = .37; p = .0095) but not in low back pain or control subjects or all groups combined. Our finding suggests that common factors appear to control digit growth and aggression predisposition and that these factors are expressed more strongly in type 2 diabetics. These findings add to the increasing body of evidence that indicates that sex steroids may play a significant role in the etiology of type 2 diabetes.